Os deuses dançam no Quilombo dos Palmares: as dimensões de análise no espaço sagrado na Serra da Barriga em Alagoas - Silva, Rafael de Lima (Sacrilegens, 2020)
Studies on the religious phenomenon have been relevant to understand spheres intertwined with the sacred: economics, politics and culture. The appropriation of spaces is part of an ethos built and modeled by a range of discourses that come from the transcendent, or as many prefer, from the sacred space. Our article aims to carry out a hermeneutics of the sacred, both in descriptive and normative terms, instrumentalized to understand the axis of African religion in the annual event in Serra da Barriga, in the municipality of União dos Palmares - AL. As methodological foundations, we use the combination of locational and epistemological geographical theories, by Zeny Rosendahl (2009) and Gil Filho (2008), as well as other names in Science and History of Religions, and also in Theology. Culminating in the research of the years 2017, 2018 and 2019.